New methods for proportional-integral controller design for time-delay systems - Aye Taiwo Ajiboye; Jayeola Femi Opadiji; Abdulrahman Olalekan Yusuf; Olusogo Joshua Popoola; Esther Toyin Olawole; Olalekan Femi Adebayo (Institute of Advanced Engineering and Science, 2022)
The development of structured methods for proportional-integral (PI) controller design for systems with time delay are proposed in this article. Several PI controller design methods for time-delay systems have been reported. However, combining two or more methods to form new ones have not been given serious attention. The system stability region in the controller parameters space was determined by plotting the stability boundaries. In this study, the controller gains were first obtained using genetic algorithm (GA), weighted geometric center (WGC), and centroid of convex stability region (CCSR). Thereafter, these gains were combined by finding the centroids of lines joining any of the two gain locations, and triangle whose vertices are the location of the three gains in the convex stability region, thus yielding four additional methods, M1, M2, M3, and M4. Compared to a particular existing method, some of the proposed methods yield faster response speed at the expense of reference input tracking, while the reverse is the case for others. Any of the proposed methods (M1, M2, M3, and M4) can be selected depending on the system performance specifications.